INTERVENÇÕES NA ASSISTÊNCIA AO PARTO POR RESIDENTES DE ENFERMAGEM DE UMA MATERNIDADE NORDESTINA: ESTUDO TRANSVERSAL. - Cruz, Pablo Nascimento; Filho, Rivaldo Lira; Freire Lima, Kassya Fernanda; Lindoso, Raylene Frazão; Soeiro, Teresa Costa; Araújo, Thaynara Pinheiro; Torres, Janete Brasil; Carneiro Alves de Oliveira, Bruno Luciano; Neto, Marcelino Santos; Costa Rabelo, Poliana Pereira (Enfermagem Atual in Derme)
Introduction: Childbirth care has undergone significant changes in recent times, although unnecessary interventions continue to be applied. It is essential to study the characteristics associated with these interventions to seek improvements in practice. Objective: To analyze the factors associated with childbirth care interventions in a public maternity hospital in northeastern Brazil, between November 2022 and March 2023. Method: A cross-sectional study conducted with pregnant women assisted by obstetric nursing residents during labor in a public maternity hospital in northeastern Brazil. Data were obtained from delivery records, newborn books, and medical charts. Relative and absolute frequencies were calculated for categorical variables, which were associated with childbirth interventions using Fisher's exact test and Prevalence Ratio (PR). Results: The study included 132 pregnant women, with interventions occurring in 90.9% of births. Most of the parturients were between 20 and 30 years old (52.3%), single (85.6%), of mixed race (53.4%), and without formal employment (75.0%). The variable education level showed a significant association with interventions (p-value=0.022). The presence of peripheral venous access had a strong association with the outcome (p-value<0.001; PR=2.5). Conclusion: Most pregnant women underwent obstetric interventions, which were mainly associated with lower education levels and the presence of venous catheters, highlighting the need for continuous improvements in obstetric practices.